Strategies for building world-class universities in Yemen with specific reference to the Malaysian experience - Al-Haimi, Basheer Mohammed Mohammed (2019)
Creating World-Class Universities (WCUs) has become a global obsession over the past decade. Governments around the world have placed higher education and research system development at the heart of their national economic strategies. Therefore, for any country, whether developed or developing, building at least one world–class University is necessary to achieve prosperity of the nation. Although a few studies about world-class universities have been conducted, this study is the first empirical study. In this study, researcher aimed to develop a strategy for building world-class universities in Yemen taking into consideration the experience of Malaysia in this particular field. To achieve this goal, this study has taken two directions of investigation. The first direction was to investigate the current situation of Yemen higher education institutions and the factors that hamper YHEIs from being listed among World-Class universities. The data for this portion of the study was gained through qualitative method with interview data. The interview data was obtained through in-person and phone interview with five top Management of the Ministry of Yemen higher education. The second direction was to find out the success factors that could led the Malaysian universities to compete and became world-class universities in a short time. This second direction was obtained by quantitative data throughout questionnaire distributed to the top management of the Malaysian universities. Using quantitative data and by applying the resource based view theory supported by contingency theory, this study aimed to investigate the relationship between the world-class university characteristics and its world-class status in Malaysian universities. This study also determines the influence of National Leadership and National Strategic Plan as moderating variables on the relationship between world-class characteristics of the university and its world class status. A judgment/purposive sampling technique was applied to collect data from top management employees in 28 public and private universities in Malaysia. The sample consist of 126 respondents of the top management in the Malaysian universities. A PLS structural equation modelling software was applied to examine the direct and moderating effects hypotheses. Results of this study succeeded to support hypothesized relationship between world-class university characteristics and Malaysian university status. Concentration of Talent, favourable Governance and Abundant Resources were found to have a significant relationship with the Malaysian university world-class status. National Strategic Plan and National Leadership was found to moderate the relationship by strengthening the relationship between the concentration of talent, favorable governance and abundant resources and Malaysian universities status. Theoretical and practical implications were discussed and several insights for future research were identified and proposed. In brief, this research helped to produce strategies for building world-class universities in Yemen learning from the Malaysian experience, which saves time and cost of the Yemen higher education policy makers. Among the recommendations are 1) Adopting the Malaysian strategic plan 2007-2010, 2011-2015 and 2015-2025 especially the transformation agenda and establishing the Apex universities, 2) the factors (quality of students, staff, researchers, good governance and abundant resources) that have been examined in this study represents success factors to gain WCUs which Yemen should follow and apply.